Contesting Religion The Media Dynamics of Cultural Conflicts in Scandinavia - Lundby, Knut (De Gruyter, 2018)
As Scandinavian societies experience increased ethno-religious diversity, their Christian-Lutheran heritage and strong traditions of welfare and solidarity are being challenged and contested. This book explores conflicts related to religion as they play out in public broadcasting, social media, local civic settings, and schools. It examines how the mediatization of these controversies influences people's engagement with contested issues about religion, and redraws the boundaries between inclusion and exclusion. FEATURED CONTRIBUTORS Lynn Schofield Clark, Professor of Media, Film, and Journalism at the University of Denver, Colorado, USA Marie Gillespie, Professor of Sociology at the Open University, Birgit Meyer, Professor of Religious Studies at Utrecht University, the Netherlands